Polarårboken Glacier (Polarboken, 2018)
Keywords: Antarktis; geografi; glasiologi

I Roald Amundsens fotspor til Sydpolen med besøk på Bettytoppen - Furholt, Astrid (Polarboken, 2018)
Keywords: Antarktis; ekspedisjoner; historie

Antarctic environmental protection: strengthening the links between science and governance - Hughes, Kevin A; Constable, Andrew; Frenot, Yves; López-Martinez, Jerónimo; McIvor, Ewan; Njåstad, Birgit; Terauds, Aleks; Liggett, Daniela; Roldan, Gabriela; Wilmotte, Annick; Xavier, José C (Environmental Science & Policy, 2018)
The Antarctic has significant environmental, scientific, historic, and intrinsic values, all of which are worth protecting into the future. Nevertheless, the area is subject to an increasing level and diversity of human activities that may impact these values within marine, terrestrial and cryosphere environments. Threats to the Antarctic environment, and to the aforementioned values, include climate change, pollution, habitat destruction, wildlife disturbance and non-native species introductions. Over time, a suite of legally binding international agreements, which form part of the Antarctic Treaty System (ATS), has been established to help safeguard the Antarctic environment and provide a framework for addressing the challenges arising from these threats. Foremost among these agreements are the Protocol on Environmental Protection to the Antarctic Treaty and the Convention on the Conservation of Antarctic Marine Living Resources. Many scientists working in Antarctica undertake research that is relevant to Antarctic environmental policy development. More effective two-way interaction between scientists and those responsible for policy development would further strengthen the governance framework, including by (a) better communication of policy makers’ priorities and identification of related science requirements and (b) better provision by scientists of ‘policy-ready’ information on existing priorities, emerging issues and scientific/technological advances relevant to environmental protection. The Scientific Committee on Antarctic Research (SCAR) has a long and successful record of summarizing policy-relevant scientific knowledge to policy makers, such as through its Group of Specialists on Environmental Affairs and Conservation (GOSEAC) up to 2002, currently the SCAR Standing Committee on the Antarctic Treaty System (SCATS) and recently through its involvement in the Antarctic Environments Portal. Improvements to science-policy communication mechanisms, combined with purposeful consideration of funding opportunities for policy-relevant science, would greatly enhance international policy development and protection of the Antarctic environment.
Keywords: Antarktis; miljøvern

The moral limits of territorial claims in Antarctica - Mancilla, Alejandra (Ethics & International Affairs, 2018)
By virtue of the Antarctic Treaty, signed in 1959, the territorial claims to Antarctica of seven of the original signatories were held in abeyance or “frozen.” Considered by many as an exemplar of international law, the Antarctic Treaty System has come to be increasingly questioned, however, in a very much changed global scenario that presents new challenges to the governance of the White Continent. In this context, it is necessary to gain a clearer understanding of the moral weight of those initial claims, which stand (despite being frozen) as a cornerstone of the treaty. The aim of this article is to offer an appraisal of such claims, which may be divided into two main kinds: those grounded on some relevant link to the territory, and those grounded on official documents and geographical doctrines. After pointing to the limitations and challenges that they face, I conclude with some remarks about how this assessment ought to serve as a starting point to rethink the territorial status of Antarctica.
Keywords: Antarktis; historie; jus; politikk; ressurser

Kapten Roald Amundsen: I vargskinnspäls och textil. Blir först på Sydpolen - Norén, Karl-Gunnar (Polarfararnas kläder : på liv och död, 2018)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; polarekspedisjoner; utstyr

Psychological Hibernation in Antarctica - Sandal, Gro Mjeldheim; van deVijver, Fons J. R.; Smith, Nathan (Frontiers in Psychology, 2018)
Human activity in Antarctica has increased sharply in recent years. In particular during the winter months, people are exposed to long periods of isolation and confinement and an extreme physical environment that poses risks to health, well-being and performance. The present study aimed to gain a better understanding of processes contributing to psychological resilience in this context. Specifically, the study examined how the use of coping strategies changed over time, and the extent to which changes coincided with alterations in mood and sleep. Two crews (N = 27) spending approximately 10 months at the Concordia station completed the Utrecht Coping List, the Positive and Negative Affect Schedule (PANAS), and a structured sleep diary at regular intervals (x 9). The results showed that several variables reached a minimum value during the midwinter period, which corresponded to the third quarter of the expedition. The effect was particularly noticeable for coping strategies (i.e., active problem solving, palliative reactions, avoidance, and comforting cognitions). The pattern of results could indicate that participants during Antarctic over-wintering enter a state of psychological hibernation as a stress coping mechanism.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

Versatility of GC-Orbitrap mass spectrometry for the ultra-trace detection of persistent organic pollutants in penguin blood from Antarctica - Warner, Nicholas; Cojocariu, Cristian; Scientific, ThermoFisher (2018)
Using GC Orbitrap mass spectrometry to address analytical challenges with trace level detection of persistent organic pollutants in Antarctica.
Keywords: Antarktis; biologi; miljøgifter; pingviner; zoologi